Cross-cultural differences through subjective cognition: illustration in translatology with the SSTIC-E in the UAE - Stip, Emmanuel; Al Mugaddam, Fadwa; Abdel Aziz, Karim; Amiri, Leena; Javaid, Syed Fahad; Arnone, Danilo; Almheiri, Eisa; Al Helali, Abdulla; Oulhaj, Abderrahim; Statsenko, Yauhen; Ljubisavljevic, Milos R.; Wanigaratne, Shamil; et al. (Frontiers in Psychology, 2024)
The development of appropriate and valid multicultural and multilingual instruments research is necessary due to a growing multicultural and multilingual society in the 21st century. We explored the use of a cognitive scale related to subjective complaints focusing on the first step a cross-cultural and semantic validation. This study presents the translation and cross-validation process of the “Subjective Scale to Investigate Cognition in Schizophrenia” (SSTICS) for the United Arab Emirates (UAE) region via different languages used in Dubaï/Abu Dhabi. This scale measures the cognitive complaints and has been validated with psychosis and used in 20 clinical trials worldwide. It evaluates areas of the illness related to self-awareness focusing on memory dysfunction and deficits of attention, language, and praxis. We described the method of cross-cultural validation, with back-translation, semantic steps, and societal contexts. The use of the SSTICE (Subjective Scale to Investigate Cognition Emirates) was explored with different samples of UAE Arabic speakers subjects. First, a pilot sample mean SSTICS total score was 16.5 (SD:16.9); (p<0.001). The SSTIC-E was then administered with 126 patients and 84 healthy control participants. The healthy group has a lower mean score of 22.55 (SD = 12.04) vs 34.06 (SD = 15.19). Method was extended to nine other languages: Pakistani/Urdu, Hindi, Marathi, Lithuanian, Serbian, German, Romanian, Sinhala, and Russian. The scales are provided in the article. The overall aim of the translation process should be to stay close to the original version of the instrument so that it is meaningful and easily understood by the target language population. However, for construct validity, some items must be adapted at the time of translation to ensure that the questioned cognitive domain is respected. For example, cooking, an executive function, does not have the same occurrence for an Emirati male, or reminding a prime minister’s name, semantic memory, requires an electoral system to appoint the leader of a country. Translation methods and processes present many challenges but applying relevant and creative strategies to reduce errors is essential to achieve semantic validation. A study aims to measure personally experienced knowledge or attitudes; such language effects can be a thorny problem.